Positive Rights In The Constitution? - Naidu, Jayanthi (Journal of Malaysian and Comparative Law, 2003)
The concrete application and elucidation of constitutional rights is not self-evicent or static. Interpretation of constitutinal rights by the courts meets the demands of a rapidly fast moving society by subscribing to the notion that the constitution is a "living document". It is worth remembering that when the 1957 Merdeka constitution was drafted, "life" in Article 5 was not contemplated to mean "livelihood". Yet, this is what the constitution provides for today. This understanding is an important as the constitution will inevitably find itself hard-pressed to meet current needs.